2022
DOI: 10.3168/jds.2021-21192
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective effects of sphingomyelin-containing milk phospholipids in ultraviolet B–irradiated hairless mice by suppressing nuclear factor-κB expression

Abstract: Ceramide-containing phospholipids improve skin hydration and barrier function and are ideal for use in skin care products. In this study, we evaluated the photoprotective effect of milk phospholipids on the skin condition of UVB-irradiated hairless mice. Skin parameters were assessed following oral administration of milk phospholipids. The UVB irradiation induced photoaging in mice. The animals were divided into 5 groups: a control group (oral administration of saline with no UBV irradiation), UVB group (oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…UVB radiation causes dehydration of the skin tissue, which breaks down the skin barrier and causes skin aging [ 8 ]. Therefore, hydration is important for maintaining the normal functioning of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…UVB radiation causes dehydration of the skin tissue, which breaks down the skin barrier and causes skin aging [ 8 ]. Therefore, hydration is important for maintaining the normal functioning of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that exogenous phosphatidylcholine accelerates the wound healing process, allowing keratinocytes to complete proliferation and migration to form a new layer of keratin in a relatively short period of time 24 . Oral administration of lactophospholipids to hairless mice exposed to UV‐B radiation‐induced photoaging resulted in downregulation of protein expression of nuclear factor kappa‐B (NF‐κB) and phosphorylated IκB‐α (κB‐α inhibitor), a significant decrease in the expression of pro‐inflammatory cytokines, especially tumour necrosis factor‐α, and improved skin hydration and barrier function 25 . The skin barrier‐improving effect of lactoferrin appears to be associated with the activation of Nrf2‐keap1, which is associated with ROS scavenging.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Oral administration of lactophospholipids to hairless mice exposed to UV‐B radiation‐induced photoaging resulted in downregulation of protein expression of nuclear factor kappa‐B (NF‐κB) and phosphorylated IκB‐α (κB‐α inhibitor), a significant decrease in the expression of pro‐inflammatory cytokines, especially tumour necrosis factor‐α, and improved skin hydration and barrier function. 25 The skin barrier‐improving effect of lactoferrin appears to be associated with the activation of Nrf2‐keap1, which is associated with ROS scavenging. Lactoferrin activates Nrf2 and increases the expression of the antioxidant enzyme HO‐1, thereby reducing ROS produced by UV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are highly reactive molecules that can damage cell structures such as nucleic acids, lipids, and carbohydrates (Birben et al 2012). Physiologically, aberrant increases in ROS production have been demonstrated to be associated with various disorders, including premature aging, inflammation, skin dryness, and skin cancer (Ichihashi et al 2003;Ahn et al 2022). Intracellular ROS are sustained at a certain level by both enzymatic and non-enzymatic antioxidant systems present in the cell (Nimse et al 2015).…”
Section: Introductionmentioning
confidence: 99%